Genetic Association Of Aurora Kinase Gene (Aukra T>A) Polymorphism With Oscc - Krishna B, Ashwin; Murthykumar, Karthikeyan (Journal of Neonatal Surgery, 2024)
Background: Aurora kinase A (AURKA) is a serine/threonine kinase that plays a pivotal role in mitotic spindle assembly, centrosome maturation, and chromosomal segregation. Disruption or upregulation of AURKA checkpoints can induce genetic instability and aneuploidy, serving as a critical driver in tumorigenesis. This study aimed to investigate the genetic association between the AURKA gene (T>A) polymorphism (rs2273535) and Oral Squamous Cell Carcinoma (OSCC) in a South Indian population. Materials and Methods: A cross-sectional study was conducted utilizing venous blood samples from 100 participants partitioned into clinical groups, including a group of cases and periodontally healthy controls (n=25 per evaluated sub-cohort). Genomic DNA was isolated using a modified Miller's protocol. Polymerase Chain Reaction (PCR) amplification was executed using custom primers spanning the polymorphic site, yielding a 165 bp amplicon, followed by restriction fragment length polymorphism (RFLP) digestion utilizing the ApoI endonuclease. Genotype frequencies, allele distributions, and Hardy-Weinberg Equilibrium (HWE) compliance were statistically analyzed using Chi-Square tests and Odds Ratios (OR) via SPSS software. Results: The distribution of the AURKA rs2273535 polymorphism conformed to HWE in both cohorts (P > 0.05). Genotype frequencies for the case group were 0% for AA, 52% (n=13) for AT, and 48% (n=12) for TT. For the control group, frequencies were 0% for AA, 60% (n=15) for AT, and 40% (n=10) for TT. Statistical evaluation revealed no significant variation in overall genotype distribution between cases and controls (χ^2, P = 0.5688). Furthermore, allele frequency shifts (T vs. A) showed no statistically significant correlation with elevated risk profile under dominant (P = 1.0000), recessive (P = 0.5693), or individual allelic (P = 0.6562) models. Conclusion: The findings demonstrate that the AURKA (rs2273535) gene polymorphism is not significantly associated with a susceptibility to oral lesions within the evaluated sample size. While AURKA aberrations remain a critical hallmark in broad human malignancies, larger multi-ethnic studies with expanded cohorts are required to fully elucidate its explicit synergistic impact on OSCC risk progression...